The validity of military screening for mental health problems: diagnostic accuracy of the PCL, K10 and AUDIT scales in an entire military population. Issue 1 (16th December 2014) - Searle, Amelia K.; Van Hooff, Miranda; McFarlane, Alexander C.; Davies, Christopher E.; Fairweather‐Schmidt, A. Kate; Hodson, Stephanie E.; Benassi, Helen; Steele, Nicole
Abstract Depression, alcohol use disorders and post‐traumatic stress disorder (PTSD) are serious issues among military personnel due to their impact on operational capability and individual well‐being. Several military forces screen for these disorders using scales including the Kessler Psychological Distress Scale (K10), Alcohol Use Disorders Identification Test (AUDIT), and Post‐traumatic Stress Disorder Checklist (PCL). However, it is unknown whether established cutoffs apply to military populations. This study is the first to test the diagnostic accuracy of these three scales in a population‐based military cohort. A large sample of currently‐serving Australian Defence Force (ADF) Navy, Army and Air Force personnel (n = 24, 481) completed the K10, AUDIT and PCL‐C (civilian version). Then, a stratified sub‐sample (n = 1798) completed a structured diagnostic interview detecting 30‐day disorder. Data were weighted to represent the ADF population (n = 50, 049). Receiver operating characteristic (ROC) analyses suggested all three scales had acceptable sensitivity and specificity, with areas under the curve from 0.75 to 0.93. AUDIT and K10 screening cutoffs closely paralleled established cutoffs, whereas the PCL‐C screening cutoff resembled that recommended for US military personnel. These self‐report scales represent a cost‐effective and clinically‐useful means of screening personnel for disorder. Military populations may need lower cutoffs than civilians to screen for PTSD. Copyright © 2014 John Wiley & Sons, Ltd.